PATH-12. DIFFUSE HEMISPHERIC GLIOMA, H3 G34-MUTANT: A COMPREHENSIVE SEQUENCING AND HIGH-RESOLUTION GENOME-WIDE COPY NUMBER ANALYSIS. (14th November 2022) - Trejo-Lopez, Jorge; Kollmeyer, Thomas; Praska, Corinne; Raghunathan, Aditya; Giannini, Caterina; Vaubel, Rachael; Nguyen, Aivi; Jentoft, Mark; Donev, Kliment; Zheng, Gang; DiGuardo, Margaret; Kipp, Benjamin; et al.
Abstract: Diffuse hemispheric glioma, H3 G34-mutant (DHG_H3G34) is a novel tumor type in the 2021 WHO CNS classification. We describe a comprehensive sequencing and high-resolution genome-wide copy number analysis of a series of cases clinically tested by a single laboratory (2018-2022). Cases included tumors from 47 unique patients (1 reportedly recurrent) that had an H3-3A G34 mutation detected using an 187-gene mutation and fusion targeted neuro-oncology NGS panel (n=47). A subset (n=18) of cases was also tested Oncoscan chromosomal microarray. Median age at testing was 20 years (range, 12-50). H3-3A G34 mutations included G34R (n=44; 94%), G34V (n=2) and a novel G34E variant considered to be likely clinically relevant (n=1). All DHG_H3G34 were hemispheric tumors, and one tumor was multifocal with midline involvement. Concurrent mutations recurrently involved ATRX (n=38), TERT promoter (n=3; mutually exclusive with ATRX mutations), TP53 (n=43), PDGFRA (n=26), PTEN (n=5), NF1 (n=4, all patients over 20 years), PIK3CA (n=4) and CDKN2A (n=3). The single recurrent tumor also had an MSH6 mutation, and in addition to 3 other cases, had increased number of sequence variants suggestive of a high tumor mutational burden. A single case also showed an FGFR3::FAM184B (exon 17::exon 2) fusion. All cases with available chromosomal microarray data had unbalanced genomes with multiple chromosomal gains/losses, and regions of copy-neutral loss of heterozygosity. The most frequent recurrent (at least 50% of cases) abnormalities were losses involving 3q, 4q, 10q, 13q and 18q, and 17p copy-neutral loss of heterozygosity encompassing TP53 (all but one case had concomitant TP53 mutation), a pattern reminiscent of IDH-mutant astrocytomas. Oncogene amplifications (PDGFRA and PIK3CA) were detected in 3 (of 18) cases. CDKN2A/B deletion was observed in 8 cases (2 homozygous). In conclusion, we describe additional sequence and copy-number abnormalities in DHG_H3G34, expanding the spectrum of genetic changes associated with this novel tumor type.